2015
DOI: 10.1038/srep15410
|View full text |Cite
|
Sign up to set email alerts
|

Aβ42-oligomer Interacting Peptide (AIP) neutralizes toxic amyloid-β42 species and protects synaptic structure and function

Abstract: The amyloid-β42 (Aβ42) peptide is believed to be the main culprit in the pathogenesis of Alzheimer disease (AD), impairing synaptic function and initiating neuronal degeneration. Soluble Aβ42 oligomers are highly toxic and contribute to progressive neuronal dysfunction, loss of synaptic spine density, and affect long-term potentiation (LTP). We have characterized a short, L-amino acid Aβ-oligomer Interacting Peptide (AIP) that targets a relatively well-defined population of low-n Aβ42 oligomers, rather than si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 78 publications
4
34
0
Order By: Relevance
“…We have previously shown that a short, 8‐residue Aβ42‐oligomer interacting peptide (AIP) can suppress the aggregation of low‐order Aβ42 oligomers into fibrils in vitro , as well as neutralize Aβ42‐induced neurotoxicity in cell cultures and rat hippocampal slices (Barucker et al . ). We have now used the Drosophila ‘rough eye’ model to investigate the long‐term efficacy of AIP in a full longitudinal study comparing male to female flies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We have previously shown that a short, 8‐residue Aβ42‐oligomer interacting peptide (AIP) can suppress the aggregation of low‐order Aβ42 oligomers into fibrils in vitro , as well as neutralize Aβ42‐induced neurotoxicity in cell cultures and rat hippocampal slices (Barucker et al . ). We have now used the Drosophila ‘rough eye’ model to investigate the long‐term efficacy of AIP in a full longitudinal study comparing male to female flies.…”
Section: Discussionmentioning
confidence: 97%
“…While the intact mass for D‐AIP (941 m /z ) was still evident at this point, the conversion of intact L‐AIP (941 m /z ) to a smaller metabolite (750 m /z ) appeared to correlate with the loss of the functionally important N‐terminal arginine (Barucker et al . ). Knowing that L‐amino acid peptides typically exhibit decreased biostability compared to D‐amino acid peptides (Tugyi et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They had previously shown that this peptide prevents the fibrillization of Aβ oligomers. In slice culture, they found that AIP prevented a loss of dendritic spines and a decrease in long-term potentiation (LTP) [ 46 ].…”
Section: Slice Culture To Study Prion-like Mechanisms In Alzheimermentioning
confidence: 99%
“…2C). As controls, we used the driver gmr-Gal4 to obtain flies expressing Aβ42 only in the retina, which leads to a 'rough eye' phenotype but does not impair brain function (Costa et al, 2011;Prüßing et al, 2013;Wang et al, 2015;Barucker et al, 2015). Similarly to the data shown in Fig.…”
Section: Knockout Of Sap47 Reduces Lifespanmentioning
confidence: 99%